2018
DOI: 10.21552/edpl/2018/4/6
|View full text |Cite
|
Sign up to set email alerts
|

Contesting Automated Decisions:

Abstract: General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of private study or research. • You may not further distribute the material or use it for any profit-making activity or commer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 12 publications
0
12
0
1
Order By: Relevance
“…170 In order to ensure strong public support, such a discussion should include various stakeholders. Norms on what 'ought' to be considered a reasonable decision is context dependent, 171 and guidelines should address the domains in which automated decision-making systems are employed (e.g., content personalization, medical assistants), the effects of such systems to various stakeholders, and the measures of oversight to be set in place. In this sense, modular guidelines would guide developers through how to decide which outputs are or are not reasonable in a given context; this task requires not only knowledge of why and when decision-making is reasonable, but also why and when an alternate decision is not made.…”
Section: Modular Guidelines For Reasonable and Legitimate Decisions By Machinesmentioning
confidence: 99%
“…170 In order to ensure strong public support, such a discussion should include various stakeholders. Norms on what 'ought' to be considered a reasonable decision is context dependent, 171 and guidelines should address the domains in which automated decision-making systems are employed (e.g., content personalization, medical assistants), the effects of such systems to various stakeholders, and the measures of oversight to be set in place. In this sense, modular guidelines would guide developers through how to decide which outputs are or are not reasonable in a given context; this task requires not only knowledge of why and when decision-making is reasonable, but also why and when an alternate decision is not made.…”
Section: Modular Guidelines For Reasonable and Legitimate Decisions By Machinesmentioning
confidence: 99%
“…Uma primeira solução para esse problema consiste na adoção de técnicas de projeto para sistemas computacionais que assegurem que estes operem de forma compatível com a lei. É o caso de abordagens de proteção de dados by design 30 e de técnicas por elas inspiradas, como contestability by design (ALMADA, 2019;BAYAMLIOĞLU, 2018;HILDEBRANDT, 2019) ou ethics by design (DIGNUM et al, 2018;ALMADA;ATTUX, 2018). Essas abordagens, em particular aquelas voltadas à proteção da privacidade, já são adotadas com variados graus de sucesso, mas enfrentam duas dificuldades principais: a possibilidade de conflitos entre os valores que essas abordagens tentam implementar (ALMADA; ATTUX, 2018; FEENBERG, 30 O artigo 25 do GDPR estabelece a necessidade de que sistemas adotem, por padrão e já desde o momento de sua concepção, medidas para a proteção de dados pessoais de seus usuários.…”
Section: Direito Computávelunclassified
“…In recent research interpreting Article 22 (3), it is suggested that the ability to contest an outcome will be aided by algorithmic systems being designed to support contestability [5,8,55]. There is acknowledgment that not just the final decision should be rendered contestable, but the entire decision-making process [8].…”
Section: 22mentioning
confidence: 99%
“…In recent research interpreting Article 22 (3), it is suggested that the ability to contest an outcome will be aided by algorithmic systems being designed to support contestability [5,8,55]. There is acknowledgment that not just the final decision should be rendered contestable, but the entire decision-making process [8]. Almada [5] proposes that to ensure data subjects are provided with the rights the GDPR seeks to protect, including self-determination, contestation should not only be considered a post-decision mechanism, such as an appeal process.…”
Section: 22mentioning
confidence: 99%
See 1 more Smart Citation